Towards fuzzy logic-based erroneous AND-gateways detection and quality assessment of BPMN models - Kopp, Andrii Mykhailovych; Godlevskyi, Mykhailo Dmytrovych; Orlovskyi, Dmytro Leonidovych (Харківський національний університет радіоелектроніки, 2025)
This paper proposes the idea of fuzzy logic-based erroneous Parallel Gateways detection and quality assessment of BPMN models, since incorrect parallel workflow executions may cause errors both in business process models and in real organizational activities.
Keywords: quality assessment; parallel (and) gateways; fuzzy logic; quality assessment